Nanostructured biomaterials for cranio-maxillofacial and oral applications - Souza, Júlio C.M.; Hotza, Dachamir; Henriques, Bruno; Boccaccini, Aldo R. (Elsevier Inc., 2018)
Nanostructured Biomaterials for Cranio-maxillofacial and Oral Applications examines the combined impact of materials science, biomedical and chemical engineering, and biology to provide enhanced biomaterials for applications in maxillo-facial rehabilitation and implantology. With a strong focus on a variety of material classes, it examines material processing and characterization techniques to decrease mechanical and biological failure in the human body. After an introduction to the field, the most commonly used materials for cranio-facial applications, including ceramics, polymers and glass ceramics are presented. The book then looks at nanostructured surfaces, functionally graded biomaterials and the manufacturing of nanostructured materials via 3-D printing. This book is a valuable resource for scientists, researchers and clinicians wishing to broaden their knowledge in this important and developing field.
CRIS-Team Scopus Importer:2022-08-05